Endothelial nitric oxide deficiency results in abnormal placental metabolism. (October 2022) - George, Hannah; Steeves, Katherine L.; Mercer, Grace V.; Aghaei, Zahra; Schneider, Céline M.; Cahill, Lindsay S.
Abstract: Placental metabolism determines the amount of nutrients available to the fetus and may be altered in pregnancies complicated by fetal growth restriction (FGR). To study which metabolites are associated with FGR, we performed 1 H high-resolution magic angle spinning magnetic resonance spectroscopy of placental tissue from endothelial nitric oxide synthase knockout (eNOS KO) mice, a model of FGR, and C57BL/6J controls at embryonic day 17.5 ( n  = 24/genotype). The relative concentration of glucose was increased in the placentas of eNOS KO mice compared to controls (p = 0.006). This study highlights the potential for glucose as a biomarker of abnormal placental metabolism that leads to FGR. Highlights: 1 H HRMAS MRS is a promising method to study placental metabolism. Glucose concentration was elevated in the placentas of growth-restricted murine fetuses. Glucose has potential to be a biomarker of abnormal placental metabolism.